(untitled) (Journal of Asian Development Studies, 2024)
This study deeply analyzes the complex relationship between internal factors, such as farmers’ existing computer knowledge, and adoption within the context of Pakistan’s agricultural sector. To collect the data from a random sample of 416 farmers drawn from Punjab Province’s five agro-ecological zones, surveys were conducted on computer knowledge and adoption intentions. The results would then reveal that although farmers still enjoy the benefits associated with computers, they actually require better skills on some specified hardware and related services in order to conduct prime activities such as assessing e-portals, online market search, and keeping financial, livestock, business planning, and payroll records. Specifically, the study outcomes go beyond those of the conventional adoption models since it shows that behavioral intentions could directly formed by a influence of prior knowledge. The study points to targeted interventions by extension professionals and policymakers towards preparing the farmers with all the computer skills required in their work, promoting digital inclusion towards the eventual development of agriculture.